Institutional foundations of agricultural development in Ethiopia: drawing lessons from current practice for agricultural R&D - German, L.; Ayele, Seife; Mazengia, W; Tsegaye, M.; Abere, K.; Bedane, K.; Geta, E.; Tolera, T.; Taye, H. (2008)
The historical emphasis on technological innovation as a pathway to rural development has obscured the institutional foundations of development – in this case, the role of local and external organizations in shaping patterns of benefits capture. Agrarian communities have a host of ways in which they self-organize to buffer themselves from economic hardship, facilitate access to limited resources and foster social cohesiveness. Yet these forms of collective action often remain invisible to development actors. External agricultural research and development organizations also play an important role in structuring development pathways and opportunities for some while marginalizing others. They also tend to create new social structures at the community level, rather than build upon existing social capital to channel its potential as a driver of development. This paper summarizes research on the development and natural resource management functions of local organizations in the highlands of Ethiopia, and on the role of local and external organizations in structuring patterns of opportunity. Three key findings are highlighted, namely: that wealth tends to beget wealth, requiring concerted attempts to support resource-poor households; that local organizations tend to produce more equitable outcomes than external development organizations; and that local organizations for natural resource management (NRM) are deficient, despite the prevalence of local NRM concerns. Implications for agricultural research and development include the need to build upon the strengths of local institutions; make the practices of external development organizations more equitable; minimize the effect of existing wealth on the potential for wealth creation; and strengthen local organizational capacities to address commonly felt NRM concerns.